P116 Increased airflow limitation during nocturnal respiratory events is associated with increased psychomotor vigilance task lapses in obstructive sleep apnoea patients. (9th November 2022) - Staykov, E; Mann, D; Duce, B; Kainulainen, S; Leppänen, T; Töyräs, J; Sands, S; Terrill, P
Abstract: Introduction: Impaired daytime vigilance is common in obstructive sleep apnoea (OSA) patients. However, the apnoea-hypopnea index (AHI) has been shown to have a weak correlation with daytime vigilance. This may be because the AHI only quantifies respiratory event frequency. Thus, we aimed to test our hypothesis that increased airflow limitation during nocturnal respiratory events is associated with daytime vigilance impairment. Methods: 495 OSA patients (AHI≥5) completed a psychomotor vigilance task (PVT) and in-lab polysomnographic recording. The number of lapses (response time >500ms) was the primary outcome. Airflow limitation was quantified from nasal airflow using a validated algorithm. Linear regression models were adjusted for age, sex, and body mass index. Results: The percentage of flow-limited breaths during respiratory events was associated with the number of PVT lapses (R=0.119, p<0.05); AHI was not (p>0.05). One standard deviation (SD, 20%) increase in the percentage of flow-limited breaths during respiratory events increased the number of lapses by 2.5. This effect-size was greater than that for age (one SD increase, 12.5 years, increased the number of lapses by 1.3). These results were similar after adjusting for AHI, arousal index, and desaturation event area. Similar findings were observed using the percentage of flow-limited breaths during all sleep. Discussion: Increased airflow limitation during nocturnal respiratory events was associated with decreased daytime vigilance in OSA patients. This association appeared to be independent of respiratory event frequency, arousal frequency, and hypoxaemia severity. This suggests that disproportionately large ventilatory drive versus achieved ventilation (i.e. flow-limitation) contributes to daytime vigilance impairment.